EFFECTIVENESS OF COMPETENT APPROACH IN ORGANIZING PRESCHOOL EDUCATION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This article describes in detail the specific features of the competence approach in the organization of the educational process in the preschool education system and information about the use of modern innovative activities in preschool education organizations. Also, competence, basic competences and the essence of educational activities in pre-school education organizations are revealed.